DAMPAK PERUBAHAN STATUS SOSIAL TERHADAP UPACARA RAMBU SOLOâ€™ DI KELURAHAN TONDON MAMULLU KECAMATAN MAKALE KABUPATEN TANA TORAJA - Patadungan, Ellyn; Purwanto, A.; Waani, Fonny J. (Universitas Sam Ratulangi, 2020)
Rambu Soloâ€™ is a traditional ceremony of the death of the Toraja people who aims to respect and deliver the spirits of the deceased to the spirit realm. At first the festive party was only carried out by the nobility, but now it has begun to shift, who is rich is what the party is festive. This study is entitled â€The Impact of Changes Social status towards Rambu Solo ceremony in Tondon Mamullu Village, Makale District, Tana Toraja District